Informal Caregiving Patterns in Korea and European Countries: A Cross-National Comparison - Soong-Nang Jang, RN, PhD; Mauricio Avendano, PhD; Ichiro Kawachi, MD, PhD (Elsevier, 2012)
Purpose: This ecological study examined demographic and institutional differences in informal caregiving. We conducted a cross-national study about the characteristics of informal caregivers in 12 European countries and Korea. Methods: Data were collected from individuals aged 50 years and older participating in the 2004/2005 Survey of Health, Ageing and Retirement in Europe and the 2006 Korean Longitudinal Study of Ageing. We examined the associations between informal caregiving and macrolevel characteristics (gross domestic product, total fertility rates, labor force participation rates, level of women's empowerment, long-term care resources). Results: Korea and some southern European countries, notably Spain and Italy, had high percentages of women, homemakers, coresidents, and spouses in informal caregiving roles. In contrast, Northern European countries such as Denmark and Sweden had high proportions of employed informal caregivers. Lower female labor force participation was associated with higher proportions of women caregivers. A higher proportion of women caregivers in the population were also associated with a lower national gross domestic product per capita. Conclusion: Our findings suggest that several contextual and institutional variables are associated with the proportion of women participating in caregiving.